2022
DOI: 10.3390/nu14224886
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic Role of the Next-Generation Probiotic Strain L. lactis MG1363-pMG36e-GLP-1 on Parkinson’s Disease via Inhibiting Ferroptosis

Abstract: Parkinson’s disease (PD) is a neurodegenerative disease (NDD) with high and ongoing morbidity, bringing heavy burdens to PD patients seriously. Finding neurotrophic drugs still remains vital due to the limited drug spectrum available currently. Substantial evidence suggests that glucagon-like peptide 1 (GLP-1) exerts neuroprotection on PD, yet the short-lived biological activity markedly hindered its application. Herein, we investigated the neurotrophic role of the next-generation probiotic strain L. lactis MG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 53 publications
(67 reference statements)
1
26
0
Order By: Relevance
“…In addition, Akk has been shown to attenuate cognitive impairment and brain amyloid-beta deposition in an APP/PS1 mice model of Alzheimer’s disease [ 13 ]. Our previous study showed that the reduction of dopaminergic neurons in mice after MPTP modeling was accompanied by a decrease of Akk abundance in the intestine [ 7 ], which is consistent with the vast majority of studies to date [ 41 , 42 , 43 ]. However, some studies have observed an increase in Akk in the gut of PD patients [ 44 , 45 , 46 ].…”
Section: Discussionsupporting
confidence: 87%
“…In addition, Akk has been shown to attenuate cognitive impairment and brain amyloid-beta deposition in an APP/PS1 mice model of Alzheimer’s disease [ 13 ]. Our previous study showed that the reduction of dopaminergic neurons in mice after MPTP modeling was accompanied by a decrease of Akk abundance in the intestine [ 7 ], which is consistent with the vast majority of studies to date [ 41 , 42 , 43 ]. However, some studies have observed an increase in Akk in the gut of PD patients [ 44 , 45 , 46 ].…”
Section: Discussionsupporting
confidence: 87%
“… 111 It has been suggested that β-hydroxybutyrate and the probiotic strain L. lactis MG1363-pMG36e-GLP-1 have the potential to modulate lipid peroxidation-driven ferroptosis by targeting ACSL4, thereby benefiting the treatment of PD. 112 , 113 Additionally, phospholipase iPLA2β (PLA2G6) was shown to inhibit ROS-induced ferroptosis by scavenging oxidized PUFAs tails in phospholipids, 114 , 115 and its inactivation or deficiency leads to PD-related motor deficits. 116 …”
Section: Discussionmentioning
confidence: 99%
“…SYXK (Zhe) 2021-0033). We utilized thirty-two 12-week-old male C57BL/6 mice according to the previous studies [ 28 , 29 ] for consistent progression of PD symptoms, each weighing approximately 25 g, procured from SLAC, Shanghai, China (License No. SCXK (Hu) 2017-0005).…”
Section: Methodsmentioning
confidence: 99%